Post mortem ethanol detection in corpses after embalming - preliminary study - Marcin Tomsia; Joanna Nowicka; Elżbieta Chełmecka (Śląski Uniwersytet Medyczny w Katowicach, 2022)
Nowadays, embalming has become more popular as it is often performed due to sanitary, hygienic, or psychological reasons. In special circumstances, like transporting a corpse from abroad, embalming is an administrative requirement. Embalming is performed using chemical substances that inhibit enzymes, bacteriological activity, and therefore cease decomposition processes. The study shows the toxicological analyses of sampled materials collected during post mortem examinations performed on six corpses subjected to the embalming process. It also presents the concentration of used preservatives in the tissues and body fluids. Analysis performed using gas chromatography with a flame ionization detector (GC-FID) revealed that in five cases, the deceased were intoxicated with ethanol during the time of death, and liquid chromatography-mass spectrometry (LC-MS) excluded the presence of psychoactive substances in all six cases. The results showed that in cases of toxicological analyses of embalmed corpses, it is crucial to secure isolated body fluids, such as cerebrospinal fluid, vitreous humor, and a wide range of reference material.